2009
DOI: 10.1177/1066896909346270
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Aberrations in Soft Tissue Tumors Harvested From Fresh Tissue Submitted for Surgical Pathology: A Single Institutional Experience

Abstract: Cytogenetic analysis demonstrated abnormal karyotypes in nearly half of this series of mesenchymal neoplasms, the majority of which consisted of recognized aberrations reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…3 Karyotyping has shown the main difference to be the presence of the (X;18) translocation. 3 Many previous studies [4][5][6] have also demonstrated the role of conventional karyotyping in the detection of clonal aberrations in 68% of malignant fibrous histiocytomas, and 38 to 48% of heterogeneous soft tissue sarcomas. Our study aimed to highlight the use of conventional karyotyping as a genome-wide screening tool, and also as an adjuvant diagnostic tool in the validation of histological diagnosis for soft tissue tumours.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Karyotyping has shown the main difference to be the presence of the (X;18) translocation. 3 Many previous studies [4][5][6] have also demonstrated the role of conventional karyotyping in the detection of clonal aberrations in 68% of malignant fibrous histiocytomas, and 38 to 48% of heterogeneous soft tissue sarcomas. Our study aimed to highlight the use of conventional karyotyping as a genome-wide screening tool, and also as an adjuvant diagnostic tool in the validation of histological diagnosis for soft tissue tumours.…”
Section: Discussionmentioning
confidence: 99%
“…These aberrations may be characterised by chromosomal gains or losses, balanced or unbalanced translocations, deletions or insertions, ring or marker chromosomes, or multiple complex karyotypes. 6 Sarcomas may be categorised into two major cytogenetic groups: (i) sarcomas with tumour-specific chromosomal alterations and simple karyotypes 2,10,11 or (ii) sarcomas with nonspecific chromosomal alterations and complex unbalanced karyotypes. 2 For group (i), karyotypes are considered to be tumour-specific or recurrent if the abnormality is found in two or more cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations